Load balancing in Microsoft Azure : practical solutions with NGINX and Microsoft Azure - Nugara, Arlan (O'Reilly Media, 2019)
With more and more companies moving on-prem applications to the cloud, software and cloud solution architects alike are busy investigating ways to improve load balancing, performance, security, and high availability for workloads. This practical report describes Microsoft Azure's load balancing options and explains how NGINX can contribute to a comprehensive solution. Cloud solution architect Arlan Nugara takes you through the steps necessary to design a practical solution for your network. Software developers and technical managers will learn how these technologies have a direct impact on application development and architecture. While the examples are specific to Azure, these load balancing concepts and implementations also apply to cloud providers such as AWS, Google Cloud Platform, DigitalOcean, and IBM Cloud. Understand load balancing--what it is and why it's important Explore load balancing in Azure, including the traffic manager and application gateway Learn how NGINX Plus on Azure lets you create an ideal end-to-end application platform Walk through three load balancing options with Azure and NGINX Plus Explore security choices including NGINX management, NGINX Web Application Firewall, and Azure Firewall integration.